Right to reprint in the Internet age - Rutecka, Daria (Studia Iuridica Toruniensia, 2019)
This article covers the topic of reprinting rights, especially in relations to entities operating on the Internet. The main subject of analysis is the issue of determining which entities are entitled pursuant to Article 25 of the Polish Copyright Act. The article concerns the matters relating to the definition of press and legal situation of blogs.